Pitiful rooftop solar uptake in sunny South Africa: A policy, funding and service delivery perspective - McKay, Tracey; Hendricks, Donavan (Frontiers in Sustainable Cities, 2022)
Abstract Despite rolling blackouts, high electricity prices, a favourable climate and the size of the South African economy, rooftop photovoltaic (PV) solar products have low levels of middle income residential market penetration. This study sought to establish why. It was found, firstly, that households opt for demand side management tools such as energy efficient lamps or inverters. Secondly, they switch to gas (at least for cooking) or a generator. Thirdly, rooftop PV is expensive, as batteries and inverters are costly. In this regard, middle income households need support measures such as feed-in tariff funding, tax rebates and subsidies. In addition, financial institutions are reluctant to finance rooftop PV, return on investment (ROI) is extremely long term and there are few, if any, bank-accredited PV suppliers. Nor is there political pressure on banks to provide attractive PV financing. Furthermore, middle income consumers struggle to understand PV technology and do not trust the suppliers thereof. For instance rooftop PV companies seldom market themselves or their products well and most do not sell PV with a maintenance service plan or offer credit. It is recommended that rooftop PV companies offer innovative modular PV packages and build their brand to create a relationship of trust with the community to increase sales.